ANALISIS PENGGUNAAN ANTIBIOTIK PADA PASIEN ANAK DI RUANG THERESIA RUMAH SAKIT ST. ELISABETH SEMARANG DENGAN METODE ATC/DDD - Rukminingsih, Fef; Apriliyani, Apriliyani (Jurnal Riset Kefarmasian Indonesia, 2021)
The high incidence of infectious diseases causes the use of antibiotics to increase. Inappropriate use of antibiotics will lead to resistance. Infectious diseases are included in the top 10 diseases in pediatric patients at St. Elisabeth Hospital.Semarang. This study aims to evaluate the use of antibiotics in pediatric patients in the Theresia ward of St. Elisabeth Hospital Semarang. This research is a descriptive observational study using retrospective data. Data were taken from medical records of pediatric patients in the Theresia ward at St. Elisabeth Hospital Semarang, aged 6 months - 14 years, the use of antibiotic therapy during the period October - December 2019. The data obtained were analyzed by calculating the quantity of antibiotic use using the Anatomical Therapeutic Chemical (ATC) and Defined Daily Dose (DDD)) / 100 patient-days methods. Based on the results of tracing medical record data, it was found that the number of pediatric patients in the Theresia room at St. Elisabeth Semarang for the period October - December 2019 is 385. The number of patients who received a single antibiotic was 162. The total value of DDD / 100 patient-days in the Theresia ward of St. Elisabeth Hospital Semarang for the period October - December 2019 is 18.17 with a total length of stay of 1117 days. The antibiotic with the highest DDD / 100 patient-days was ceftriaxone, namely 15.10. While the antibiotics that enter the DU 90% segment are ceftriaxone and cefotaxime.